2017
DOI: 10.1038/mp.2017.246
|View full text |Cite
|
Sign up to set email alerts
|

Markers of microglia in post-mortem brain samples from patients with Alzheimer’s disease: a systematic review

Abstract: Neuroinflammation is proposed as one of the mechanisms by which Alzheimer’s disease pathology, including amyloid-β plaques, leads to neuronal death and dysfunction. Increases in the expression of markers of microglia, the main neuroinmmune cell, are widely reported in brains from patients with Alzheimer’s disease, but the literature has not yet been systematically reviewed to determine whether this is a consistent pathological feature. A systematic search was conducted in Medline, Embase and PsychINFO for arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
263
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(314 citation statements)
references
References 195 publications
27
263
3
Order By: Relevance
“…Although IBA1 is recognized as an effective pan‐microglial marker , more subtle changes in activation including phagocytic status may have been missed. For example, other human post‐mortem studies have demonstrated upregulation of major histocompatibility complex class II (MHC II) and cluster of differentiation 68 (CD68), markers of activation and phagocytosis, respectively; see review .…”
Section: Discussionmentioning
confidence: 99%
“…Although IBA1 is recognized as an effective pan‐microglial marker , more subtle changes in activation including phagocytic status may have been missed. For example, other human post‐mortem studies have demonstrated upregulation of major histocompatibility complex class II (MHC II) and cluster of differentiation 68 (CD68), markers of activation and phagocytosis, respectively; see review .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been recent discussion as to whether these microglia are activated or dystrophic and which form is mostly likely to be causative in the relevant pathological changes (Navarro et al ). Even considering a possible activated state, evidence suggest that both markers of M1 and M2 activation states are present in AD (Hopperton et al ). Other studies suggest both activation states are present at different times (Tang and Le ).…”
Section: Roles Of Microglia In Neurodegenerationmentioning
confidence: 99%
“…Single‐cell RNA‐sequencing studies also suggest that there is continuous, heterogeneous spectrum of states present in the brains of mouse models of AD (von Maydell and Jorfi ). A comparison of microglial markers between individuals with AD and high‐pathology but cognitively normal controls showed that microglial activation is increased in AD, suggesting that microglial activation is not simply a reaction to AD pathology such as β‐amyloid deposition (Hopperton et al ). It is possible that microglia are pushed towards a more pro‐inflammatory phenotype through age‐related changes.…”
Section: Roles Of Microglia In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, microglia activation patterns are region specific in both AD and MDD. While a range of markers associated with microglia activation (CD68, MHCII, ionized calcium‐binding adapter molecule 1, , and CD11c) are broadly overexpressed in the frontal, orbitofrontal, cingulate, and temporal cortices of biopsied AD brains (Hopperton, Mohammad, Trépanier, Giuliano, & Bazinet, ), their activation pattern (IL‐1 receptor) in the parahippocampal cortex has laminar specificity, particularly in layers III–IV (Sheng, Griffin, Royston, & Mrak, ). Characterization of microglia activation in AD patients using PET imaging with 18 FEPPA binding to mitochondrial also supports the presence of inflammatory or phagocytic microglia in the anterior cingulate cortex (ACC), temporal cortices, multiple frontal gyri, and striatal regions (Edison et al, ).…”
Section: Common Immune Pathwaysmentioning
confidence: 99%